Kształtowanie innowacyjności produktów żywnościowych poprzez sposób ich pakowania - Matysik-Pejas, Renata (Creating the Innovation of Foodstuffs by Wrapping, 2006)
Innovation is defined in marketing depending on an adopted point of reference with market, enterprise, product or consumer. To be notified as novelty by consumers it is enough to change any characteristics of a product. It concerns also wrappings which are an essential element of product image and decide about it functionality and availability. Technological solutions which can be used in wrappings cause, that product gains new usefulnesses. The aim of the paper is to present results of an analysis of consumers' opinion of chosen aspects concerning innovative solutions in foodstuffs wrappings.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 120-127